Roles of Major Histocompatibility Complex Class II in Inducing Protective Immune Responses to Influenza Vaccination - O, Eunju (American Society for Microbiology, 2014)
Major histocompatibility complex class II-deficient (MHC-II KO; Aβ(−/−)) mice were used to assess the roles of MHC-II molecules in inducing protective immune responses to vaccination. After vaccination with influenza A/PR8 virus-like particle (VLP) vaccine, in vivo and in vitro vaccine antigen-specific IgG isotype antibodies were not detected in MHC-II KO mice, which is quite different from CD4 T cell-deficient mice that induced vaccine-specific IgG antibodies. The deficiency in MHC-II did not significantly affect the induction of antigen-specific IgM antibody in sera. MHC-II KO mice that were vaccinated with influenza VLP, whole inactivated influenza virus, or live attenuated influenza virus vaccines were not protected against lethal infection with influenza A/PR8 virus. Adoptive transfer of fractionated spleen cells from wild-type mice to MHC-II KO mice indicated that CD43(+) cell populations with MHC-II contributed more significantly to producing vaccine-specific IgG antibodies than CD43(−) B220(+) conventional B cell or CD4 T cell populations, as well as conferring protection against lethal infection. Bone marrow-derived dendritic cells from MHC-II KO mice showed a significant defect in producing interleukin-6 and tumor necrosis factor alpha cytokines. Thus, results indicate that MHC-II molecules play multiple roles in inducing protective immunity to influenza vaccination. IMPORTANCE Major histocompatibility complex class II (MHC-II) has been known to activate CD4 T helper immune cells. A deficiency in MHC-II was considered to be equivalent to the lack of CD4 T cells in developing host immune responses to pathogens. However, the roles of MHC-II in inducing protective immune responses to vaccination have not been well understood. In the present study, we demonstrate that MHC-II-deficient mice showed much more significant defects in inducing protective antibody responses to influenza vaccination than CD4 T cell-deficient mice. Further analysis showed that CD43 marker-positive immune cells with MHC-II, as well as an innate immunity-simulating adjuvant, could rescue some defects in inducing protective immune responses in MHC-II-deficient mice. These results have important implications for our understanding of host immunity-inducing mechanisms to vaccination, as well as in developing effective vaccines and adjuvants.